Exploratory study on variables impacting display advertising spend of leading advertisers in the USA. Issue 2 (17th February 2021) - Chakrabarti, Somnath; Makhija, Mayank
ABSTRACT: This pioneering study comprehensively analyzes display advertising spends for large and medium-sized advertisers in the US market, the most evolved advertising and display advertising market in the world, unlike some other academic studies in the domain focusing solely on media spend trends, without focusing on the advertisers. The research objective of this study was to explore the impact of relevant variables during the growth of display advertising spend from its infancy till recent times in the US by analyzing the data on other measured media spend, product categories, US sales of advertisers, HQ Continent of advertisers, and unmeasured media spend among others. This study analyzed media data on 78 large advertisers in 12 product categories for the year 2000 to 2016 in the US market. The plm package used allowed the study to run the major types of models used for panel data like pooling, between, fixed, first differences, and random models. It analyzed a significant amount of real-world cross-sectional and longitudinal data on media spend and sales in the US market and might be relevant to senior marketing executives. Further, it gives guidance for media buyers and sellers and mentions four cases which are in line with this study.